2017
DOI: 10.3928/00220124-20170110-10
|View full text |Cite
|
Sign up to set email alerts
|

Using the Teach-Back Method in Patient Education to Improve Patient Satisfaction

Abstract: More research needs to be conducted to determine the effectiveness of teach back on HCAHPS scores. J Contin Educ Nurs. 2017;48(1):47-52.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 9 publications
1
38
0
1
Order By: Relevance
“…Active engagement in learning such as the use of teach-back strategies have been associated with improved comprehension, more patient-centered communication, and increased engagement of parents [110112]. Teach-back is a way of checking comprehension by asking patients to repeat back in their own words what they have been told by their health care provider [113]. However, further research is needed regarding the efficacy, feasibility, fidelity and acceptability of teach-back in an ED setting [112].…”
Section: Discussionmentioning
confidence: 99%
“…Active engagement in learning such as the use of teach-back strategies have been associated with improved comprehension, more patient-centered communication, and increased engagement of parents [110112]. Teach-back is a way of checking comprehension by asking patients to repeat back in their own words what they have been told by their health care provider [113]. However, further research is needed regarding the efficacy, feasibility, fidelity and acceptability of teach-back in an ED setting [112].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has often reported that health providers can be reluctant to use Teach-Back due to perceptions it can increase consultation time [ 24 , 43 , 47 49 ]. We did not report impact on call duration, because during the study period nurses were encouraged to focus on practising Teach-Back skills rather than meeting call duration targets, and skill learning may have temporarily inflated average call duration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research with healthcare providers has identified four key barriers to delivering Teach-Back: perceived time constraints [ 24 , 31 – 34 ], quantity and complexity of information discussed [ 35 ], discomfort with phrasing [ 34 , 36 ] (including consumer-reported discomfort [ 37 ]), and divided attention (of parents) [ 34 , 35 ]. Enablers to the use of Teach-Back include a supportive work environment and practitioner self-reflection [ 38 ].…”
Section: Introductionmentioning
confidence: 99%